BENCANA DAN PELESTARIAN HUTAN: PERSEPSI KULTURAL MASYARAKAT PINGGIRAN HUTAN TAMAN NASIONAL MERU BETIRI - Krisnadi, Krisnadi (Historia, 2018)
This paper aims to explore the cultural perceptions Madurese and Javanese ethnic at Sanenrejo and Sarongan Village on forests functionas biological sources, illegal logging, natural disasters due to deforestation, and forest conservation in the Meru Betiri National Park. Such problems are significant because the forests functions as the lungs of the world, balancing climate, strengthening the ozone layer, holding wind, tackling lands lides and floods, storing rain water, and as a tourism object. They reject acts of illegal logging, because it can damage forests and cause natural disasters. Therefore, they participate in conservation of Meru Betiri National Park. Keywords: Meru Betiri National Park; cultural perceptions; forest conservation; disaster; illegal logging; Javanese and Madurese ethnic